"The Same Force, Authority, and Effect": Formalizing Native Property and British Plurality in Lower Canada. (January 2016) - Lewandoski, Julia
Abstract : In 1790s Lower Canada, British officials pursued a pluralist land tenure policy, establishing new Loyalist freehold townships while allowing the French seigneurial estate system to continue. The extension of French land tenure into the British era also made the status of Native land highly ambiguous. This was a legacy of Jesuit mission involvement with Native villages in the St Lawrence Valley, and of the fluidity of indigenous landholding within French land tenure in general. This case study of two Abenaki Indian places in 1790s Lower Canada demonstrates some unexpected British responses to these complexities. Scholars typically emphasize British colonial desires for consistent, coherent land tenure in general, and preference for freehold land tenure in particular. Yet in their treatment of Abenaki land, British authorities sustained French ambiguities and even created a new anomaly in their own township system. Rather than masking these varieties, British surveyors chose to display the uncertainty, plurality, and anomaly of Native land tenure on the maps they made of Abenaki land.